2023
DOI: 10.3389/fpubh.2022.1079347
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the health satisfaction of users of public health and medical institutions in South Korea

Abstract: IntroductionIn this study, we investigated the health satisfaction levels of users of regional health and medical institutions in South Korea and the influencing factors.MethodsWe included randomly selected 300 people with experience in using health and medical institutions from panel data targeting the entire nation. We used questionnaire (EQ-5D-5L) and sociodemographic characteristics to analyze the health satisfaction. EQ-5D-5L was used to measure health-related quality of life in five areas: mobility, self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…For job satisfaction, the job satisfaction questionnaire of [26], which was modified and used by 'The index of work Satisfaction' developed by [27], was used. Each question was composed of a 5-point scale that it was not at all, it was normal, it was yes, and it was very yes, and the higher the score, the higher the job satisfaction.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…For job satisfaction, the job satisfaction questionnaire of [26], which was modified and used by 'The index of work Satisfaction' developed by [27], was used. Each question was composed of a 5-point scale that it was not at all, it was normal, it was yes, and it was very yes, and the higher the score, the higher the job satisfaction.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…As of the end of December 2020, it was found that the relevant services had been provided to 169,391 out of the 1,591,827 health checkup result cases. [19][20][21][22][23] At the community level, regional health and medical institutions play an important role in reducing disease and enhancing health levels. Furthermore, the data linkage between each system can be effectively utilized because it has no data collection cost or responding burden.…”
Section: Introductionmentioning
confidence: 99%